Emerging Legal Issues in the Taxation of Personal Incomes in Nigeria - Ierkwagh, Kwaghkehe (ABUAD Law Journal, 2019)
The legal framework for personal income taxation in Nigeria is the Personal Income Tax Act, 2004 (as amended in 2011). However, the taxation of personal incomes in Nigeria as provided under the Personal Income Tax Act presents a lot of practical and conceptual legal issues ranging from the legal implications and justifications for the exemption of certain personal incomes from tax liability under the Act, the tax rates, and the issue as to whether the taxation of dividends constitute double taxation. Through the doctrinal research method, this paper has established that apart from equity considerations, the exemption of incomes of registered friendly societies, ecclesiastical and charitable societies from tax has eroded the tax base by creating opportunities for tax avoidance and evasion since incomes of their members or leadership may be concealed as incomes of those organizations, that the legal basis for the exemption of profits of cooperative societies has collapsed and no longer in tune with modern commercial realities, and that the graduated tax rates as provided under the Act is bound to serve as disincentive to work and also encourage labour agitations for better working conditions. It is therefore recommended that the Personal Income Tax Act be amended to clearly draw a difference between incomes of the exempted bodies and their members so as to subject incomes of members to tax, and that the taxation of dividends, though not double taxation be imposed at a low rate, while the graduated tax rates be lowered so that taxpayers may voluntarily comply with their tax obligation with the smallest amount of hissing while government revenue improves significantly.